Preservation of crestal bone by implant design. A comparative study in minipigs. Issue 3 (19th June 2012) - Heitz‐Mayfield, L. J. A.; Darby, I.; Heitz, F.; Chen, S.
Abstract Objectives To compare crestal bone modeling at three bone level design implants; Astra Tech Osseospeed™ Implant (AOI), Straumann® Bone Level Implant (SBLI) and NobelReplace™ Tapered Groovy Implant (NBTI). Materials and methods In 12 minipigs one implant of each design was placed on each side of the mandible with submerged healing. The implant platform was placed at the level of the crest (Group 0), and 1 mm above the crest (Group + 1 mm). In addition, one Straumann® Tissue Level Implant STLI was placed as a control on each side of the mandible. At 4 weeks, six animals were sacrificed. In the remaining six animals healing abutments were connected until 12 weeks. Clinical, radiographic, and histologic analyses were made. ANOVA and Mann–Whitney U‐tests were used to evaluate differences in bone levels between implant designs. Results At 4 weeks there was no statistically significant difference in bone changes between implant designs. At 12 weeks implants in Group + 1 mm had minimal bone changes with no differences between implant designs. In Group 0, the AOI and SBLI preserved more crestal bone than NBTI (P < 0.01). Mean distance from the implant platform to the buccal bone was −0.1 ± 0.2 mm for AOI, −0.3 ± 0.3 mm for SBLI, and −1.0 ± 0.3 mm for NBTI. Mean radiographic bone levels from the implant platform were −0.1 ± 0.4 mm for AOI, 0.0 ± 0.3 mm for SBLI and −0.9 ± 0.8 mm for NBTI. Conclusion Greater bone preservation was observed for the AOI and SBLI compared with the NBTI.